Why use qualitative research methods to understand the meaning of clients’ experiences in healthcare research? - Lee, Khuan; Krauss, Steven Eric (Community Health Society Malaysia, 2015)
Clients’ health experience influence their health behaviour and decision making in accepting medical care and treatment provided. Thus, it is importance for health care professionals to grasp meaning embedded in clients’ health experience to assist them to achieve individual health goals. This article is aimed to elucidate what and why reasons health care professionals are required to use qualitative research method to understand clients’ health experience.